Complete Occlusion of Bilateral Internal Carotid Artery in a Marijuana Smoker: A Case Report - Sharma, Dikshya (J Clin Med Res, 2019)
Here we described a case of a young male who developed stroke attributable to heavy marijuana smoking. Although, instances of stroke due to cannabis smoking have been reported earlier, this case is distinctive due to the fact that the patient had bilateral complete occlusion of internal carotid artery (ICA) at a very early age. In view of studies that have correlated marijuana smoking to intracranial stenosis and atherogenesis, this case of bilateral ICA occlusion illustrates the severity and burden of the disease.